Slow deep breathing exercise untuk mengurangi nyeri selama pelepasan water seal-drainage (WSD) pada pasien pneumothorax - Novia Wulansari; Fitrian Rayasari; Dewi Anggraini (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Health problems are one of the big problems that result in an increase in the death rate in the world. One of them is a case of pneumothorax, especially spontaneous pneumothorax. Pneumothorax is defined as the presence of air in the chest cavity and specifically in the pleural cavity. WSD is a special tube that is inserted into the pleural cavity using a trocar or surgical clamp. Insertion of a WSD is a painful and frustrating experience for the patient. Studies show that patients who undergo installation experience pain ranging from moderate to severe. Slow deep breathing can stimulate autonomic nervous responses through the release of endorphin neurotransmitters which have an effect on reducing sympathetic nerve responses which function to increase body activity and increase parasympathetic responses to reduce body activity. Non-pharmacological slow deep breathing exercise therapy can be given in 5 to 10 minutes per day. Providing slow deep breathing relaxation therapy for 15 minutes can reduce the intensity of pain.Purpose: To know effectiveness EBNP Slow Deep Breathing Exercise (SDBRE) to reduce pain during and during the release of Water Sealed Drainage (WSD)Method: Quantitative research using quasi-experimental with a repeated-measures design on respiratory disorder intervention patients who had water sealed drainage (WSD) installed at the Persahabatan General Hospital, East Jakarta in May - June 2023 with a sample size of 20 participants. The instruments in this research are educational media in the form of leaflets and learning videos about the slow deep breathing exercise intervention and the pre and post assessment instruments for EBNP implementation, namely the Visual Analogue Scale (VAS), which is to measure participants' pain levels before (pre) intervention and after (post) slow intervention deep breathing exercise.Results: Shows that the intervention and control groups have differences in the mean pain levels. In the intervention group it was 2,366 while in the control group it was 3,100, so the mean difference between the two groups was 0.734, which means there is a large difference between the two groups. This is caused by the treatment given. The p-value is 0.001 < 0.005, so according to the basis of decision making in the test it can be concluded that Ho is rejected, which means that there is an effect of giving slow deep breathing exercise intervention which can affect pain.Conclusion: Independent nursing intervention in the form of deep and slow breathing exercises for patients with respiratory disorders who have installed water sealed drainage (WSD) at Persahabatan General Hospital has a significant effect in reducing pain.Keywords: Pain Intensity, Pneumothorax; Relaxation Therapy; Water Sealed Drainage (WSD).Pendahuluan: Masalah kesehatan merupakan salah satu permasalahan besar yang mengakibatkan terjadinya peningkatan angka kematian di dunia. Salah satunya ialah kasus pneumothorax terutama pneumothorax spontan. Pneumothorax diartikan sebagai adanya udara di rongga dada dan secara spesifik berada pada rongga pleura. WSD adalah pipa khusus yang dimasukkan ke rongga pleura dengan perantaraan trokar atau klem penjepit bedah. Pemasangan WSD merupakan hal yang menyakitkan dan pengalaman yang membuat frustasi bagi pasien. Studi menunjukkan bahwa pasien yang menjalani pemasangan mengalami nyeri mulai dari skala sedang sampai berat. Slow deep breathing dapat merangsang respon saraf otonom melalui pelepasan neurotransmiter endorfin yang berpengaruh terhadap penurunan respon saraf simpatis yang berfungsi meningkatkan aktivitas tubuh dan meningkatkan respon parasimpatis untuk menurunkan aktivitas tubuh. Terapi non farmakologi slow deep breathing exercise dapat diberikan dalam waktu 5 sampai 10 menit perhari. Pemberian terapi relaksasi nafas dalam lambat selama 15 menit dapat menurunkan intensitas nyeri.Tujuan: Untuk mengetahui efektivitas Slow Deep Breathing Exercise (SDBRE) untuk mengurangi nyeri selama dan saat pelepasan Water Sealed Drainage (WSD)Metode: Penelitian kuantitatif menggunakan quasi-experimental dengan desain repeated-measures pada pasien intervensi gangguan respirasi yang terpasang water sealed drainage (WSD) di Rumah Sakit Umum Persahabatan Jakarta Timur pada bulan Mei - Juni 2023 dengan jumlah sampel 20 partisipan. Instrumen dalam penelitian ini yaitu media edukasi berupa leaflet dan video pembelajaran intervensi slow deep breathing exercise dan instrumen penilaian pre dan post pelaksanaan EBNP yaitu Visual Analogue Scale (VAS) yaitu untuk mengukur tingkat nyeri partisipan sebelum (pre) intervensi dan setelah (post) intervensi slow deep breathing exercise.Hasil: Menunjukkan kelompok intervensi dan kontrol terdapat selisih nilai rerata tingkat nyeri. Pada kelompok intervensi 2.366 sedangkan pada kelompok kontrol 3.100, sehingga nilai beda mean kedua kelompok 0.734 yang artinya terdapat selisih yang jauh antara kedua kelompok. Hal ini disebabkan oleh sebuah perlakuan yang diberikan. Nilai p-value sebesar 0.001 < 0.005, maka sesuai dasar pengambilan keputusan dalam uji dapat disimpulkan Ho ditolak yang artinya terdapat pengaruh pemberian intervensi slow deep breathing exercise dapat mempengaruhi nyeri.Simpulan: Intervensi keperawatan mandiri berupa latihan nafas dalam dan lambat pada pasien gangguan respirasi yang terpasang water sealed drainage (WSD) di Rumah Sakit Umum Persahabatan mempunyai pengaruh yang signifikan dalam menurunkan nyeri.